2021
DOI: 10.1186/s13287-021-02549-6
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic effect of lung-resident progenitor cells with high aldehyde dehydrogenase activity

Abstract: Background Aldehyde dehydrogenase (ALDH) is highly expressed in stem/progenitor cells in various tissues, and cell populations with high ALDH activity (ALDHbr) are associated with tissue repair. However, little is known about lung-resident ALDHbr. This study was performed to clarify the characteristics of lung-resident ALDHbr cells and to evaluate their possible use as a tool for cell therapy using a mouse model of bleomycin-induced pulmonary fibrosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…1H and List S11), we found LRRK2 which loss is linked to AT2 cell dysfunction in experimental pulmonary fibrosis (44). We also noted ALDH1A1 in this group of genes, which is associated with stemness and exert anti-fibrotic properties when highly expressed in lung epithelial cells in experimental pulmonary fibrosis models in mouse (45). Taken together, these results show that the FC-induced transcriptomic changes share similarities to those seen in IPF.…”
Section: Resultsmentioning
confidence: 79%
“…1H and List S11), we found LRRK2 which loss is linked to AT2 cell dysfunction in experimental pulmonary fibrosis (44). We also noted ALDH1A1 in this group of genes, which is associated with stemness and exert anti-fibrotic properties when highly expressed in lung epithelial cells in experimental pulmonary fibrosis models in mouse (45). Taken together, these results show that the FC-induced transcriptomic changes share similarities to those seen in IPF.…”
Section: Resultsmentioning
confidence: 79%
“…Previous studies have found that ALDH+ cells have a stemcell characteristic, often making cancer cells more resistant to common chemotherapeutic drugs. 20,23,79 This study has limitations such as dissecting the whole signaling cascade of ALDH2-mediated EMT, stemness modulation and invivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…The atRA could promote cellular proliferation, differentiation, morphogenesis, cell survival, angiogenesis, wound recovery and stem cell migration mediated by the retinoic acid receptors (RARs) [23,24]. The atRA could inhibit the brosis of lung, liver and rein [25][26][27]. The atRA could also inhibit the endometrial brosis in a rat IUA model [28].…”
Section: Discussionmentioning
confidence: 99%